Analysis Efectifity of Television Advertising As Telkomsel Prepaid Card with Epic Method Using Model and Its Effect on Consumer Attitudes in Pekanbaru - Roni Afrian Pane; Gatot Wijayanto; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was motivated by the above phenomenon proves that television still dominates share of advertising in Indonesia is a television advertising media advertising mass media that can be accessed easily than other advertising media. The study aims to find out: 1) Effectiveness of Television Advertising Telkomsel U.S. Prepaid Cards by Using Method of Consumer Attitudes Toward EPIC Model in Pekanbaru city, 2) the effect on consumer attitude EPIC Model in Pekanbaru city in the U.S. using a Vodacom prepaid card, 3) Which variables of the EPIC model which has a dominant influence on consumer attitudes in the U.S. using Vodacom prepaid card in Pekanbaru city. The study site user community cards are there in the U.S. telkomsel Pekanbaru. The reason for choosing these objects because Pekanbaru many people use the prepaid card. The population in this study is a free consumer that is in Pekanbaru are using Vodacom prepaid cards in the U.S., amounting to 245 091 Pekanbaru. Based on the above calculation, the sample in this study was 99.959 in the round it off to 100 respondents AS Telkomsel prepaid card users. The results of the research model and hypothesis testing in this study on the effectiveness of television advertising AS Telkomsel prepaid card by using models of epic on consumer attitudes in the city of Pekanbaru to the conclusion: 1) Based on the statistical significance value of the F-test probability of 2.530 and the level of significantly by 0045. It can be concluded that the variable empathy, persuasion, impact, communication, can affect people's attitudes (y). 2) Based on the calculation, the value of coefficient of determination (R2) indicates if the overall effect of the 100% 0:58% in this study could be explained by the attitude variables empathy, persuasion, impact, communication. 3) Empathy, persuasion, impact, communication together have a strong influence on the attitude of the community. Based on the value of t statistics Empathy (x1) of 1,993 in this case t-count is greater than t-table 1.98. These results suggest that empathy (X1) affect people's attitudes are demoninan.Keywords: Empathy, persuasion, impact, communication, attitude.